Secretome profile analysis of multidrug-resistant, monodrug-resistant and drug-susceptible Mycobacterium tuberculosis - Chanyanuch Putim (2018)
© 2017 Springer-Verlag GmbH Germany The emergence of drug-resistant tuberculosis has generated great concern in the control of tuberculosis and HIV/TB patients have established severe complications that are difficult to treat. Although, the gold standard of drug-susceptibility testing is highly accurate and efficient, it is time-consuming. Diagnostic biomarkers are, therefore, necessary in discriminating between infection from drug-resistant and drug-susceptible strains. One strategy that aids to effectively control tuberculosis is understanding the function of secreting proteins that mycobacteria use to manipulate the host cellular defenses. In this study, culture filtrate proteins from Mycobacterium tuberculosis H37Rv, isoniazid-resistant, rifampicin-resistant and multidrug-resistant strains were gathered and profiled by shotgun-proteomics technique. Mass spectrometric analysis of the secreted proteome identified several proteins, of which 837, 892, 838 and 850 were found in M. tuberculosis H37Rv, isoniazid-resistant, rifampicin-resistant and multidrug-resistant strains, respectively. These proteins have been implicated in various cellular processes, including biological adhesion, biological regulation, developmental process, immune system process localization, cellular process, cellular component organization or biogenesis, metabolic process, and response to stimulus. Analysis based on STITCH database predicted the interaction of DNA topoisomerase I, 3-oxoacyl-(acyl-carrier protein) reductase, ESAT-6-like protein, putative prophage phiRv2 integrase, and 3-phosphoshikimate 1-carboxyvinyltransferase with isoniazid, rifampicin, pyrazinamide, ethambutol and streptomycin, suggesting putative roles in controlling the anti-tuberculosis ability. However, several proteins with no interaction with all first-line anti-tuberculosis drugs might be used as markers for mycobacterial identification.